2023
DOI: 10.3390/biomedicines11041130
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity and Carcinogenesis: Their Relationship under the Umbrella of Autophagy

Abstract: The immune system and autophagy share a functional relationship. Both innate and adaptive immune responses involve autophagy and, depending on the disease’s origin and pathophysiology, it may have a detrimental or positive role on autoimmune disorders. As a “double-edged sword” in tumors, autophagy can either facilitate or impede tumor growth. The autophagy regulatory network that influences tumor progression and treatment resistance is dependent on cell and tissue types and tumor stages. The connection betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 453 publications
0
2
0
Order By: Relevance
“…Tumour cells exploit autophagy as a survival mechanism to adapt to unfavourable microenvironments, such as nutrient deprivation and hypoxia [ 29 ]. This strategy enables cancer cells to maintain high energy levels, mitigate oxidative stress, and evade cell death pathways, ultimately contributing to tumour progression and therapy resistance [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour cells exploit autophagy as a survival mechanism to adapt to unfavourable microenvironments, such as nutrient deprivation and hypoxia [ 29 ]. This strategy enables cancer cells to maintain high energy levels, mitigate oxidative stress, and evade cell death pathways, ultimately contributing to tumour progression and therapy resistance [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, a complex role of autophagy has been reported [ 32 ]. Rosenfeldt et al demonstrated that reduced autophagy affects melanoma growth in a manner dependent on the phosphatase and tensin homologue (PTEN) status [ 31 ]. In contrast, Xie et al showed that the deletion of autophagy-related 7 ( Atg7 ) promotes the growth of melanoma cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two-faceted relationship between cancer and autophagy is well known, presenting aspects which have been discussed from different angles in several of our articles [147][148][149][150][151][152]. Mammalian cells exploit regulatory processes between SIRTs and autophagy to maintain energetic homeostasis in response to internal and external stimuli.…”
Section: Sirt Regulation Of Autophagy In Cancer Stem Cellsmentioning
confidence: 99%
“…In the course of both these groups, there are significant disorders of the immune system, which affect not only its proper functioning but also the maintenance of immune homeostasis, the disturbance of which may result in the development of autoimmunity or cancer [31]. Research in recent years points to immunological checkpoints as key elements of the ongoing deregulation.…”
Section: Introductionmentioning
confidence: 99%